A Note on the Use of Syndicated Loan Data - Isabella Müller; Felix Noth; Lena Tonzer (Tinbergen Institute, 2022)
Syndicated loan data provided by DealScan is an essential input in banking research. This data is rich enough to answer urging questions on bank lending, e.g., in the presence of financial shocks or climate change. However, many data options raise the question of how to choose the estimation sample. We employ a standard regression framework analyzing bank lending during the financial crisis to study how conventional but varying usages of DealScan affect the estimates. The key finding is that the direction of coefficients remains relatively robust. However, statistical significance seems to depend on the data and sampling choice.
Keywords: C50; G15; G21; 330; Syndicated Lending; DealScan; Scrutiny; Meta-Analysis